Faith Beyond Optimism: Simone Weil, Hannah Arendt, and Gillian Rose - MacMillen, Sarah L. (Philosophy & theology, 2011)
This article discusses the definitions of faith of three twentieth-century Jewish-Christian mystic philosophers: Simone Weil, Hannah Arendt, and Gillian Rose. Weil’s “attente de Dieu” (waiting for God), Arendt’s “natality,” and Rose’s immanence each reflect an attention to the world in understanding the workings of faith. In this context, faith and hope are not cheap optimisms or escapisms into the transcendent, but a patient reckoning with the pains of the world and human relationships.